Attitude and Cognitive Achievement in VLab Experience of STEM Learners in Chemistry - Q. Larida, Alvin; R. Olvis, Paul; Y. Disca, Berlita; F. Docena, Aida (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Laboratory applications are of significant importance in chemistry education due to various limitations and deficiency conditions of the recent traditional laboratory. Objective: In order to address the gap, this study examined the effect of virtual laboratory (vLab) on the attitude and cognitive achievement and the relationship of these two variables with one another among 59 STEM students of eleventh-grade (control and experimental group). Methods: Study were gathered with pre and posttest using Chemistry Attitude Scale (CAS1), Cognitive Achievements Scale (CAS2) test, and augmented with semi-structured interview (ssi) for those who experienced vLab. Comparisons were made within and between groups. Using SPSS software, the mean scores, t-test, and Pearson Product correlation(r) were used to analyze the data, while thematic analysis was used for ssi result. Conclusion: It was concluded that both traditional and virtual laboratory elicited positive attitudes and average cognitive achievement among students. Moreover, the virtual laboratory is at least as effective as the traditional laboratory, both in terms of students’ attitudes and cognitive achievements. The findings showed also, that there is significant positive relationship in the students’ attitude and cognitive achievement in chemistry for both traditional and vLab groups. Furthermore, some students agreed that the vLab can help them to perform the experiments quickly, it invites their interest to move further in the activity, and can perform on their own pace. Recommendation: This also suggests that further study is needed in different domains and subscales of attitudes, development of instructional materials which focuses on Bloom’s taxonomy should be supplemented for instructions, and enhance quality virtual laboratory to be added to the pedagogy.